TINJAUAN HUKUM ISLAM TERHADAP PERSEPSI MINAT PEGAWAI MENABUNG PADA BANK KONVENSIONAL DAN BANK SYARIAH (Studi pada Pegawai Kantor Kementerian Agama Kabupaten Kolaka) - nurmiwati nurmiwati (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Some of the Kolaka community who understand about Islamic law are employees who play an active role in the Ministry of Religion agency, Kolaka Regency. However, employees in these institutions have savings at conventional banks, and some of them also have savings in Islamic banks. This is because they have their own perceptions about conventional banks and Islamic banks, which makes them have an interest in saving at conventional banks or Islamic banks. The formulation of the problem in this study is whether there is an effect of perceptions on interest in saving at conventional banks and Islamic banks? The purpose of this study was to determine whether perceptions have an influence on employee interest in saving at conventional banks and Islamic banks. The approach of this research is a quantitative approach and the type of associative research using the field data obtained. The data collection instrument uses Likert scale measurement with data collection techniques in the form of questionnaires and documentation. With the data analysis technique through the SPSS program, namely the validity, reliability, and multiple linear regression tests with three variables. The results showed that partially the perception variable towards conventional banks with a significance value of 0.893 and the perception of Islamic banks with a significance value of 0.670 did not significantly influence the interest of employees of the Ministry of Religion Office of Kolaka to save at conventional banks and Islamic banks.